Development of Discrete Wavelet Transform (DWT) toolbox for signal processing applications - Mousa K., Wali; Murugappan, M., Dr.; R. Badlishah, Ahmad, Assoc. Prof. Dr.; Bong, Siao Zheng (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/